Psikologi Pendidikan dalam Perspektif Islam dan Barat: Studi Perbandingan Teori dan Implikasinya - Widyaningsih, Erna; Muharromah, Fityatul; Rohimah, Siti (Lembaga Yasin AlSys, 2025)
Educational psychology is a branch of science that focuses on the learning process and the various factors influencing it, including cognitive, affective, and social aspects. Islamic and Western perspectives offer differing approaches to understanding educational psychology, both theoretically and in its application within educational settings. This study aims to compare educational psychology theories from Islamic and Western viewpoints and analyze their implications for educational practice. A qualitative method was employed using a literature review approach, examining relevant primary and secondary sources. The findings indicate that in the Islamic perspective, educational psychology is viewed as a process of character formation grounded in spiritual, moral, and tawḥīd-based values, with the ultimate goal of cultivating noble character (akhlāq). In contrast, the Western perspective places greater emphasis on cognitive development, behavior, and environmental influences on learning. These paradigm differences affect instructional methods, curriculum design, and the role of educators in guiding learners. The study concludes that integrating both perspectives can produce a more holistic and contextual approach to educational psychology, addressing the demands of modern education while remaining rooted in moral and spiritual values.